Analysis of Learning Media Needs in the Implementation of Online Lectures during the Covid-19 Pandemic - Muhammad Helmi Azhar; Anik Ghufron (STAI Hubbulwathan Duri, 2022)
This study aims to describe the needs of learning media that are needed by students when carrying out lecture activities through online learning during the COVID-19 pandemic. The method used in this study is a quantitative study with data collection methods through questionnaires distributed to 144 students and then analyzed by quantitative descriptive analysis. The conclusion of this article is the effectiveness of the online lecture process during the pandemic. Students' learning media needed during online lectures are mobile-based media with video, multimedia, and other graphic media that are dynamic images. It is necessary to develop learning media and learning resources that are a commodity for students to improve distance learning services.